1. Assistant professor of Psychiatry, Psychiatry and Behavioral Sciences Research Center, Mashhad University of Medical Sciences, Mashhad, Iran - Bidaki, Reza; Noshadifar, Hamideh; Shahini, Najmeh; Salimi, Zanireh (Researcher Bulletin of Medical Sciences, 2023)
Background & Objective: Cancer is a global concern, and the management of cancer patients dealing with various psychological symptoms is a growing concern. Acceptance and commitment therapy (ACT) is effective psychological management in cancer patients improving psychological symptoms. However, the effect of ACT on cancer patients' resilience and general health has not been widely studied. The present study aimed to evaluate the effect of ACT on the general health and resilience of cancer patients undergoing chemotherapy. Materials and Methods: Sixty patients with breast, lung, or colorectal cancer enrolled in the present study and allocated into intervention and control groups. The Connor-Davidson Resilience Scale (CD-RISC) and General health questionnaire (GHQ) were filled as pretest and post-test after ACT as eight sessions (each session 9') during four weeks for the intervention group and after 4-weeks for the control group. Results: The mean age of the participants was 35±76.3 years, and the mean age, gender, cancer duration, duration of receiving chemotherapy, and marital status were not significantly different among the study groups. After adjusting for baseline scores, there was a significant difference in study groups in resilience and general health scores. The effects indicate that treatment accounted for 70.9% and 62.6% of the post-test covariance of resilience and general health scores, respectively. Conclusion: ACT could be an effective psychological intervention in increasing general health and resilience among cancer patients